Estimating contemporary migration numbers of adults based on kinship relationships in iteroparous species. (22nd July 2022) - Akita, Tetsuya
Abstract: This paper describes the development of estimators for the contemporary migration number and rate of adults between two populations in iteroparous species. The proposed estimators are based on known half‐sibling (HS) and/or parent–offspring (PO) relationships observed between populations across breeding seasons. The rationale is that HS and PO pairs exhibit information about the occurrence frequency of parental movements during the breeding interval. The proposed method allows for variance in the average number of offspring per parent within and between populations. In addition, coupled with the PO pairs found within the population, the estimators can be obtained using only genetic data. Generally, a sample size representing the square root of the population size is required to obtain meaningful migration information. We describe a detailed evaluation of the performance of the proposed estimators by running an individual‐based model, and the results provide guidance regarding sample sizes to ensure the required accuracy and precision. In addition, given that there are few effective methods to estimate adult movement (especially when populations cannot be genetically distinct), we discuss the usefulness of the proposed kinship assignment method in terms of conservation biology and wildlife management.